Ecology and ecophysiology of southwestern Australian hakea species with contrasting leaf morphology and life forms. - Groom, Philip K. (Curtin University, 1996)
Members of the genus Hakea (Proteaceae) are sclerophyllous, evergreen perennial shrubs or small trees endemic to Australia, with 65% of species confined to the South-West Botanical Province (southwestern Australia). Southwestern Australian Hakea species possess two contrasting leaf morphologies (broad or terete leaves) and fire-related life forms (non-sprouting (fire-killed) or resprouting (fire-surviving)), with each species representing one of four leaf morphology-life form groups.Representative species within each group were studied to determine whether they display similar distribution and ecophysiological patterns at both the adult and seedling stages. The distribution of species within these groups was best based on averages and variations in annual temperature and rainfall. The highest percentage of terete leaved non-sprouters (25 species) occurred in areas of low-moderate rainfall with large annual temperature ranges, whereas terete leaved resprouters (14 species) displayed a patchy distribution. Broad leaved resprouters (28 species) dominated areas of strongly seasonal rainfall, with few species occurring in the drier regions. Broad leaved non-sprouters (33 species) were best represented in areas of low annual temperature. The distribution of non-sprouters/resprouters may be due to the effect of climatic factors on seedling recruitment and/or fire frequencies. Leaf morphology appears to have a more direct influence on species distribution, as broad leaves are favoured in regions of medium-high, seasonal rainfall (less stressful habitats) while terete leaves are better adapted to tolerate hot, dry environments.Terete leaves are either simple (needle-like) or 2-3 pronged, and, apart from their narrow width, are characterised by their greater leaf thickness (> 1 mm), smaller projected area and mass, higher leaf mass per area (a measure of sclerophylly) and a lower density than broad leaves. Broad leaves are much more variable in their shape. Increased leaf thickness and sclerophylly in terete leaves can be partially attributed to the presence of a central parenchyma core and increased palisade thickness. This core is surrounded a compact network of fibre-capped vascular bundles. Thickness and sclerophylly were good indicators of relative nutrient content in terete, but not broad leaves. Both leaf types have a thick cuticle (> 20 mu m) and sunken stomates, with terete leaves possessing a greater stomatal density than broad leaves. Broad leaves are bilateral and hence amphistomatous. Adult and seedling leaves (of a similar leaf type) differed in morphology, but not anatomy, with some species producing broad seedling leaves and terete adult leaves.Seedlings growing under optimal growth conditions (full sunlight, well watered) in pots showed no relationship between rate of growth and ecophysiology with respect to the four species groupings, although seedlings of non-sprouters and broad leaved species had higher transpiration and photosynthetic rates than seedlings of resprouters and terete leaved species respectively. In response to high air temperatures (> 35°C), leaf temperatures close to or lower than the surrounding air temperature only occurred for terete leaved species possessing small individual and total leaf areas. By maintaining leaf photosynthesis rates during periods of relatively high air temperatures, terete leaved seedlings were able to produce more biomass per leaf area while retaining a low leaf area per seedling mass. When subjected to periods of water stress (withholding water), differences in water relations were most evident between seedlings of non-sprouters and resprouters, with resprouter seedlings showing an ability to minimise the decrease in relative water content for a given decrease in XPP. Although terete leaves possess many xeromorphic attributes, terete leaved seedlings were not necessarily superior at avoiding/tolerating drought. Terete leaves in seedlings may have alternative heat dissipation and/or anti-herbivore properties.Seasonal water relations of adult plants were monitored for over a year, including a period of prolonged summer drought at four sites (two on laterite (rocky substrate) and two on deep sand). The eight species inhabiting the lateritic sites were more stressed (more negative xylem pressure potentials (XPP)) in summer than the eight species on sandy soils, with lower conductances and higher leaf specific resistivity (XPP/area-based transpiration, LSR). Broad leaved species had higher transpiration rates and LSR, and more negative midday XPP throughout the study than terete leaved species. When spring (predrought) and summer (drought) data were compared, non-sprouters had lower XPP in summer, and lower transpiration rates and conductances in both seasons than resprouters. Non-sprouters on lateritic sites had the lowest water relations values in summer (drought tolerators). There was a tendency for broad leaved resprouters on sandy soils to have higher summer water relations values (drought avoiders). Broad leaved non-sprouters on lateritic soils could be considered the most water stressed group, with substantial plant death during the summer period. Terete leaved species on sandy soils were the most conservative in their water usage.